The Effect of Problem-Based Learning on Students’ Mathematics Problem Solving Ability - Yulyana, Yulyana; Hamid, Hariaty; Anwar, Azwar (Journal of Mathematics and Applied Statistics, 2024)
The purpose of this study was to determine the effect of problem-based learning on students' mathematics problem solving ability at SMA Negeri 1 Tanjung Palas Tengah. This research is an experimental research with pretest- posttest control group design. The population in this study were all grade XI students at SMA Negeri 1 Tanjung Palas Tengah. The sample was drawn using cluster random sampling technique and the research sample was obtained, namely class XI IPA 1 with a total of 15 students as an experimental class and class XI IPA 2 with a total of 15 students as a control class. The data collection technique in this study was a written test. Data analysis in this study used descriptive analysis, namely the average and standard deviation and prerequisite tests, namely normality test and homogeneity test for initial data and hypothesis testing using independent sample t-test statistical test. The results of the descriptive analysis showed that the average pretest score in the experimental class was greater than the average pretest score in the control class, which was 59.87 in the experimental class while in the control class it was 52.87. While the posttest value in the experimental class was 79.93, while in the control class it was 65.33. Based on the results of the independent sample t-test analysis with a significant level of 5% (α = 0.05). Thus H0 is rejected and H1 is accepted, so it can be concluded that the problem-based learning model affects the problem solving ability of class XI students of SMA Negeri 1 Tanjung Palas Tengah.